Effectiveness of postural corrective exercise on postural improvement in students with forward head posture (FHP) - Nurhayati, Ummy A'isyah; Dewi, Eka Zinta Nurmala (Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: Forward head posture (FHP) is a postural problem in the cervical area characterized by the position of the tragus in front of the plumb line in the sagittal plane with a craniovertebral angle (CVA) value <50°. This condition can be caused by work positions or activities that tend to look down for a long duration. Postural corrective exercise is one of the exercises that can improve posture.Objective: Knowing the effectiveness of postural corrective exercise on posture improvement in students with FHP.Methods: This study used a quasi-experimental pre & post-test design. Respondents were 68 students of Universitas 'Aisyiyah Yogyakarta with CVA <50° who were then randomly divided into 2 groups. namely Group A (postural corrective exercise) and Group B (self-postural corrective exercise). CVA measurement was performed using the On Protractor application.Results: There was a significant increase in CVA after postural corrective exercise and self-postural corrective exercise treatment (p = 0.00). Postural corrective exercise is more effective in improving FHP posture than self-postural corrective exercise (p = 0.00).Conclusion: Postural corrective exercise is more effective on posture improvement in students with FHP.